Textbooks against Terrorism: How Curriculum Design Shapes Vulnerability to Extremism in Pakistan: https://doi.org/10.5281/zenodo.16886361 - Ibrahim Shah; Muhammad Uzair (`, 2025)
This study focuses on the role of the state-owned school curricula in instilling extremist ideologies by using qualitative and critical discourse analysis to study the textbook content in Pakistan. Based on current statistics (2023-2024), the study establishes patterns of systematic militarization, religiosity as exclusivity, and anti-minority bias in history, Islamic, and social studies textbooks in different provinces. The results indicate that 87 percent of reviewed texts promote that war is the Islamic obligation, 92 percent of the reviewed texts include sectarian language against minority Muslim groups, and 89 percent of the reviewed texts delete Hindu and Sikh historical contributions. The regional differences are dramatic, as the curriculum of Balochistan promotes ethnonationalism and that of Punjab encourages the hatred towards India, and these patterns also correlate with the ways of extreme localism. The paper compares these results against the peace education standards of the UNESCO and how the pedagogical approach of Pakistan institutes a form of education that promotes Type 3 Violent Extremism in the formal school system. The contrast between Indonesia and Nigeria, and Pakistan reveals effective models of curriculum deradicalization as well as the special problems the latter faces: the strong influence of the military on education policy, opposition to the deradicalization effort among religious conservatives, and the dualistic system of madrassas and public schools. In the paper, the author contends that such piecemeal, province-based reforms, as a revised social studies curriculum in Sindh are sources of viable solutions making them work, as long as structural impediments, such as the lack of teacher training and the lobbying activities of textbook publishers, are overcome. Unless reformed with immediacy, Pakistani education system is likely to continue the loop of radicalization, as it presents violence as a sacred aspect and pluralism as a dangerous factor. Keywords: Curriculum Reform, Violent Extremism, Textbook Analysis, Pakistan Education, Radicalization, Peace Education, Ideological Indoctrination, Sectarianism, Militarized Pedagogy, Comparative Education